A Distributed-Ledger Consortium Model for Collaborative Innovation. - Khan, Chris; Lewis, Antony; Rutland, Emily; Wan, Clemens; Rutter, Kevin; Thompson, Clark (Computer (00189162), 2017)
R3 has built a global consortium to focus on the application of distributed-ledger technology (DLT), which can help banks combat low return on equity and alleviate pressure on their operating costs. The authors explain the conditions that led to interest in DLT and introduce Corda, R3’s shared ledger for recording and managing financial agreements.